Pengaruh Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Kedai Tempe Mendoan Babute Bojongsari Depok - Munarsih Munarsih; Hanif Janarko (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this study was to determine the effect of Promotion and Product Quality both partially and simultaneously on Purchasing Decisions at Kedai Tempe Mendoan Babute Bojongsari Depok with a sample of 98 Respondents. The method used is a quantitative method. Data analysis used in this study is the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, T test and F test. The results of this study are Promotion has a significant effect on Purchasing Decisions on the regression Y = 2.676 + 0.936 X1, the correlation value is 0.903 meaning that the two variables have a very strong relationship. Product Quality has a significant effect on Purchasing Decisions with the regression equation Y = 3.047 + 0.920 X2, the correlation value is 0.923 meaning that the two variables have a very strong relationship. Promotion and Product Quality simultaneously have a significant effect on Purchasing Decisions with the regression equation Y = 1.503 + 0.369 X1 + 0.595 X2. The coefficient of determination value is 87.2%, while the remaining 12.8% is caused by other variables not examined in this study. The results of testing the first hypothesis obtained a calculated tvalue > ttable or (20.596 > 1.660). Based on the results of testing the second hypothesis, the calculated tvalue > ttable or (23.475 > 1.660) was obtained. Based on the results of testing the third hypothesis, the Fcount value was 322.228 > Ftable 3.092. This shows that simultaneously the Promotion and Product Quality variables have a significant influence on Purchasing Decisions